Asthma and poly(ADP-ribose) polymerase inhibition: a new therapeutic approach - Zaffini R; Gotte G; Menegazzi M (Dove Medical Press, 2018)
Raffaela Zaffini, Giovanni Gotte, Marta Menegazzi Department of Neuroscience, Biomedicine and Movement Science, Biochemistry Section, University of Verona, Verona, Italy Abstract: Asthma is a chronic lung disease affecting people of all ages worldwide, and it frequently begins in childhood. Because of its chronic nature, it is characterized by pathological manifestations, including airway inflammation, remodeling, and goblet cell hyperplasia. Current therapies for asthma, including corticosteroids and beta-2 adrenergic agonists, are directed toward relieving the symptoms of the asthmatic response, with poor effectiveness against the underlying causes of the disease. Asthma initiation and progression depends on the T helper (Th) 2 type immune response carried out by a complex interplay of cytokines, such as interleukin (IL) 4, IL5, and IL13, and the signal transducer and activator of transcription 6. Much of the data resulting from different laboratories support the role of poly(ADP-ribose) polymerase (PARP) 1 and PARP14 activation in asthma. Indeed, PARP enzymes play key roles in the regulation and progression of the inflammatory asthma process because they affect the expression of genes and chemokines involved in the immune response. Consistently, PARP inhibition achievable either upon genetic ablation or by using pharmacological agents has shown a range of therapeutic effects against the disease. Indeed, in the last two decades, several preclinical studies highlighted the protective effects of PARP inhibition in various animal models of asthma. PARP inhibitors showed the ability to reduce the overall lung inflammation acting with a specific effect on immune cell recruitment and through the modulation of asthma-associated cytokines production. PARP inhibition has been shown to affect the Th1–Th2 balance and, at least in some aspects, the airway remodeling. In this review, we summarize and discuss the steps that led PARP inhibition to become a possible future therapeutic strategy against allergic asthma. Keywords: allergic airway disease, PARP1, PARP14, remodeling, STAT6, Th1–Th2 balance, Th2 response